Friends or foes in the rhizosphere: traits of fluorescent Pseudomonas that hinder Azospirillum brasilense growth and root colonization - Maroniche, Guillermo Andrés (2018)
Bacteria of the Azospirillum and Pseudomonas genera are ubiquitous members of the rhizosphere, where they stimulate plant growth. Given the outstanding capacity of pseudomonads to antagonize other microorganisms, we analyzed the interaction between these two bacterial groups to identify determinants of their compatibility. We could establish that, when in direct contact, certain Pseudomonas strains produce lethality on Azospirillum brasilense cells using an antibacterial type 6 secretion system. When analyzing the effect of Pseudomonas spp. diffusible metabolites on A. brasilense growth on King´s B medium, we detected strong inhibitory effects, mostly mediated by siderophores. On Congo Red medium, both inhibitory and stimulatory effects were induced by unidentified compounds. Under this condition, Pseudomonas protegens CHA0 produced a Gac/Rsm-regulated antibiotic which specifically inhibited A. brasilense Sp7 but not Sp245. This effect was not associated with the production of 2,4-diacetylphloroglucinol. The three identified antagonism determinants were also active in vivo, producing a reduction of viable cells of A. brasilense in the roots of wheat seedlings when co-inoculated with pseudomonads. These results are relevant to the understanding of social dynamics in the rhizosphere and might aid in the selection of strains for mixed inoculants.